2008
DOI: 10.1093/eurheartj/ehn464
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust inhalation increases thrombus formation in man

Abstract: Inhalation of diesel exhaust increases ex vivo thrombus formation and causes in vivo platelet activation in man. These findings provide a potential mechanism linking exposure to combustion-derived air pollution with the triggering of acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
225
2
4

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(239 citation statements)
references
References 39 publications
8
225
2
4
Order By: Relevance
“…Thus, Even though both fibrinogen (Danesh et al, 2005) and air pollution (Maitre et al, 2006) have been independently shown to be positively correlated with cardiovascular morbidity and mortality, most epidemiological studies report mainly negative correlations between the air pollutants measured and fibrinogen concentrations. Unfortunately enough, the direct affect of diesel exhaust exposure on fibrinogen concentration was not reported in most of the recent human toxicological studies (Carlsten et al, 2007;Mills et al, 2007;Tornqvist et al, 2007;Lucking et al, 2008). As far as we know the only toxicological report was by Bloomberg et al (Blomberg et al, 2005) were no effect was found on fibrinogen concentrations.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Thus, Even though both fibrinogen (Danesh et al, 2005) and air pollution (Maitre et al, 2006) have been independently shown to be positively correlated with cardiovascular morbidity and mortality, most epidemiological studies report mainly negative correlations between the air pollutants measured and fibrinogen concentrations. Unfortunately enough, the direct affect of diesel exhaust exposure on fibrinogen concentration was not reported in most of the recent human toxicological studies (Carlsten et al, 2007;Mills et al, 2007;Tornqvist et al, 2007;Lucking et al, 2008). As far as we know the only toxicological report was by Bloomberg et al (Blomberg et al, 2005) were no effect was found on fibrinogen concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…In their toxicological studies in men with and without prior myocardial infarction, who were exposed to dilute diesel exhaust (300 μg per cubic meter) or filtered air for 1 hour during periods of rest and moderate exercise in a controlled-exposure facility, both Mills and Tornqvist did not show increments in serum C-reactive protein concentrations 6 or 24 hours by exposure to diesel exhaust or filtered air Tornqvist et al, 2007). Lucking et al (Lucking et al, 2008) has shown similar results when reporting his toxicological study in which no changes in plasma TNF-a, IL-6, C-reactive protein, and soluble ICAM-1 concentrations were observed. These measurements were obtained however, only 6 hours following both diesel exhaust and filtered air exposures.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Estudos recentes demonstraram que através da instilação intratraqueal aguda do PM 2,5 em ratos Wistar, na dose de 100 µg/mL e 500 µg/mL (Rivero et al, 2005a) e na dose de 50 µg/mL (Maatz et al, 2009) Em contrapartida, a literatura apresenta inúmeros estudos experimentais de toxicidade da queima do diesel (Campen et al, 2005;Anselme et al, 2007;Gottipolu et al, 2009;Saxena et al, 2009;Sunil et al, 2009) e de exposição controlada em humanos Lucking et al, 2008;Peretz et al, 2008aPeretz et al, , 2008bLangrish et al, 2009 Lucking et al, 2008;Langrish et al, 2009), a reatividade vascular (Peretz et al, 2008a) e a VFC (Peretz et al, 2008b). O compostos orgânicos da queima do diesel, são descritos como geradores de inflamação e estresse oxidativo (Ball et al, 2000;Saldiva et al, 2002;Nemmar et al, 2009;Sunil et al, 2009 Outros estudos também demonstraram que o B100 reduz as emissões de MP, CO e HC e aumenta as emissões de NO X (parâmetro não avaliado neste estudo) (EPA, 2002a;Graboski et al, 2003;Zou et al, 2003;Yuan et al, 2007;Lapuerta et al, 2008a).…”
Section: Análise Dos Hidrocarbonetos Policíclicos Aromáticosunclassified